The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0069601
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Kidney Function in HIV-Infected Adults in Kenya: Comparison to a Direct Measure of Glomerular Filtration Rate by Iohexol Clearance

Abstract: BackgroundMore than two-thirds of the world's HIV-positive individuals live in sub-Saharan Africa, where genetic susceptibility to kidney disease is high and resources for kidney disease screening and antiretroviral therapy (ART) toxicity monitoring are limited. Equations to estimate glomerular filtration rate (GFR) from serum creatinine were derived in Western populations and may be less accurate in this population.MethodsWe compared results from published GFR estimating equations with a direct measure of GFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 35 publications
(50 reference statements)
3
72
0
Order By: Relevance
“…33 As in our study, Peralta et al showed that the diagnosis of low eGFR in Blacks was very sensitive to the race coefficient used in the GFR estimating equation in the bi-racial CARDIA cohort of young adults living in the United States. the CKD-EPI and MDRD better predicted iohexol derived GFRs when the race coefficient was removed 20 and similar results were recently described in a South African population as well. 21 Furthermore, among HIV-infected women in the WIHS cohort, eGFR was substantially lower when estimated with cystatin C compared with creatinine among Black participants, whereas cystatin C and creatinine produced similar estimates among White participants.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…33 As in our study, Peralta et al showed that the diagnosis of low eGFR in Blacks was very sensitive to the race coefficient used in the GFR estimating equation in the bi-racial CARDIA cohort of young adults living in the United States. the CKD-EPI and MDRD better predicted iohexol derived GFRs when the race coefficient was removed 20 and similar results were recently described in a South African population as well. 21 Furthermore, among HIV-infected women in the WIHS cohort, eGFR was substantially lower when estimated with cystatin C compared with creatinine among Black participants, whereas cystatin C and creatinine produced similar estimates among White participants.…”
Section: Discussionsupporting
confidence: 84%
“…32 Baseline covariates were defined at entry more, several studies among Black Africans showed that removing the race coefficient improved GFR estimation compared with a gold standard. 20,21 The aim of our study was to investigate whether current eGFR equations in clinical use might systematically over-estimate the kidney function, and thus misclassify CKD status, of Black Americans with HIV. We are unaware of any large registry or cohort of Blacks living in the United States with HIV that contains gold standard GFR measures.…”
Section: Chronic Kidney Disease Risk Factorsmentioning
confidence: 99%
“…17 The CKD-EPI equation has recently been validated in African populations and provides more accurate estimates for eGFR values in the normal range than both the Modification of Diet in Renal Disease Study and Cockoft-Gault equations when compared to a direct measure of GFR by iohexol clearance. 18,19 Serum creatinine was measured at baseline, month 1, and quarterly thereafter. For this analysis, predefined study outcomes were mean eGFR change from baseline and a decline in eGFR of ≥25% compared to baseline, as confirmed by a second measurement obtained prior to study drug discontinuation.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study suggests that the CKD-EPI equation gave the most accurate estimate of iohexol clearance in 99 cART naïve patients from Kenya. 68 Proteinuria is one of the salient indicators of ongoing renal injury and is frequently present in screening tests of HIV patients. Proteinuria may be screened using urine dipsticks or spot urine protein or albumin to creatinine ratios.…”
Section: Screening For Ckd In Hiv Patientsmentioning
confidence: 99%